Influence of Green Investment, Environmental Tax and Sustainable Environment: Evidence from ASEAN Countries - Hieu, Vu Minh (International Journal of Energy Economics and Policy, 2022)
Currently, sustainable environment has become a global requirement due to the uncertainty of the environmental conditions and require researchers’ and policymakers’ attention. Therefore, the present research examines the role of green investment and environmental taxes on the sustainable environment in ASEAN countries. The researchers have also used economic growth (EG) and population growth as the control variables. The present article has used secondary sources of data collection such as the Organization for Economic Co-operation and Development (OECD) and world development indicators (WDI) and extracted secondary data from 1981 to 2020. The current research has applied the Augmented Dickey-Fuller (ADF) test to examine the stationarity and applied the panel pooled mean group (PMG) model to test the association between the constructs. The results revealed that green investment and environmental taxes have a negative linkage with carbon (CO2) emission that shows a positive linkage with the sustainable environment in ASEAN countries. The results also exposed that EG and population growth have a positive linkage with CO2 emission that shows a negative linkage with the sustainable environment in ASEAN countries. The present article has provided the guidelines to the policymakers while establishing new regulations regarding sustainable environment through green investment and environmental taxes.